(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effect of using the scramble method on students’ interest and understanding of the Al-Qur’an Hadith subject in Grade X at MAN 2 Kota Cirebon. The research was motivated by the low level of student interest and understanding, as demonstrated by a lack of active participation and difficulty in understanding the texts of the Qur’an and Hadith, which is thought to be related to the use of conventional teaching methods. This study used a quantitative approach with a non-experimental descriptive correlational design. The data were analysed to determine the relationship between the use of the scramble method as an independent variable and student interest and understanding as dependent variables. The results of the analysis showed a correlation coefficient (rxy) of 0.573, which is in the moderate correlation category and is positive, thus indicating a significant influence between the two variables. The contribution of determination was 60%, indicating that the scramble method contributed significantly to increasing student interest and understanding, with an increase of 33%. Thus, the scramble method can be used as an alternative active learning strategy in Al-Qur’an Hadith lessons.